Catalytic behavior of hexaphenyldisiloxane in the synthesis of pyrite FeS2. Issue 64 (14th July 2020) - Todd, Paul K.; Martinolich, Andrew J.; Neilson, James R.
Abstract : Hexaphenyldisiloxane acts catalytically to yield FeS2 in metathesis reactions at low temperatures (150 °C) compared to reactions with no molecule. Abstract : Functional small molecules afford opportunities to direct solid-state inorganic reactions at low temperatures. Here, we use catalytic amounts of organosilicon molecules to influence the metathesis reaction: FeCl2 + Na2 S2 → 2NaCl + FeS2 . Specifically, hexaphenyldisiloxane ((C6 H5 )6 Si2 O) is shown to increase pyrite yields in metathesis reactions performed at 150 °C. In situ synchrotron X-ray diffraction (SXRD) paired with differential scanning calorimetry (DSC) reveals that diffusion-limited intermediates are circumvented in the presence of (C6 H5 )6 Si2 O. Control reactions suggest that the observed change in the reaction pathway is imparted by the Si–O functional group. 1 H NMR supports catalytic behavior, as (C6 H5 )6 Si2 O is unchanged ex post facto . Taken together, we hypothesize that the polar Si–O functional group coordinates to iron chloride species when NaCl and Na2 S4 form, forming an unidentified, transient intermediate. Further exploration of targeted small molecules in these metathesis reaction provides new strategies in controlling inorganic materials synthesis at low-temperatures.